STRENGTHENING THE EXISTENCE OF ISLAMIC RELIGION EDUCATION IN THE INDUSTRIAL REVOLUTION ERA 4.0 (Study of PAI FAI Curriculum Review of Muhammadiyah Gresik University) - Amirudin, Noor (Tamaddun, 2019)
This study provides an overview of the importance of massive reform in the Curriculum of Islamic Religious Education at the Faculty of Islam, Muhammadiyah Gresik University. This reform is needed so that the FAI UMG PAI curriculum can answer the challenges and demands of the times that continue to change globally. Besides, this deafness also poured out the results of a solution to Islamic religious education in the face of the Era of Industrial Revolution 4.0. As it is known, that the Era of the Industrial Revolution 4.0 had a broad impact on all lines of life, including in the field of education, especially Islamic education. The era that gave birth to this disruption phenomenon demanded the world of Islamic religious education to participate in adjusting. Graduates of Islamic education are now faced with new challenges, demands, and needs that have never existed before. So it is necessary to update and innovate the system, governance, curriculum, human resource competencies, facilities and infrastructure, culture, work ethic, and others. Otherwise, Islamic religious education will be increasingly left behind and outdated. Therefore, it is necessary to look for concrete steps for Islamic religious education in order to be able to remain competitive in this disruption era. The solution step is to participate in discussing themselves. Keywords: Islamic religious education, industrial revolution 4.0, disruption